CRIMINAL PROCEDURAL ASPECTS OF THE ACTIVITIES OF INVESTIGATIVE BODIES IN FOREIGN COUNTRIES (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article examines foreign experience and practices in organizing pre-trial procedures in the form of inquiry in various countries, including some post-Soviet republics. The author emphasizes that, despite the different designs, models of inquiry, as well as the sometimespolar opinions about the need for its existence in criminal proceedings, inquiry nevertheless takes its place and plays an important role as a measure of state administration to combat manifestations of crime. In addition, the author reminds that when modernizing domestic legal systems, it is necessary to carefully borrow foreign experience and take into account the established value approaches and national traditions. The inquiry in the Kyrgyz Republic does not have a detailed regulated procedural form. In the criminal process of the Kyrgyz Republic, there is a stage of initiation of a criminal case, the inquiry is conducted in pre-trial proceedings and aims to take measures to preserve traces of the incident, carry out the instructions of the investigator, prosecutor, etc. The idea is emphasized that the problematic of the institute of inquiry requires further scientific research and investigation.
Keywords: inquiry agency, pre-trial proceedings, prosecutor, preliminary investigation, criminal prosecution, criminal procedure, procedural form